Evaluating miR-107 and adiponectin as biomarkers in obstructive sleep apnea: Associations with neurotransmitters and metabolic regulation - Asifa Ashraf; Muhammad Sarwar; Kaleem Arshad; Muhammad Ali Talat; Khudija Saleh (PLoS ONE, 2025)
This study aimed to examine the levels of microRNA-107 (miR-107) and its correlation with neurotransmitters (glutamate, serotonin, melatonin) and adiponectin in patients with obstructive sleep apnea (OSA) compared to healthy controls. The results showed that serum levels of miR107, melatonin, and adiponectin were significantly lower in OSA patients compared to controls, while serotonin and glutamate levels were significantly higher. Spearman correlation analysis revealed that in the control group, miR-107 levels were moderately correlated with glutamate (negative) and adiponectin (positive), but these associations were disrupted in the OSA group. Receiver operating characteristic (ROC) curve analysis demonstrated that miR-107 had excellent diagnostic performance, with 100% sensitivity and 89.3% specificity at a cut-off of 3.0 ng/mL. Adiponectin also showed strong diagnostic potential, with 78% sensitivity and 89% specificity. In contrast, serotonin, melatonin, and glutamate exhibited more moderate diagnostic accuracy. These findings suggest that miR-107 and adiponectin could serve as promising biomarkers for diagnosing OSA, and targeting miR-107 to modulate metabolic factors may offer novel therapeutic approaches for improving OSA management.